Covid-19 and the ‘Sarawak Way’: Surviving the pandemic? - Collin, Jerome (Universiti Malaya Press, 2023)
Recent years have witnessed a heightened interest and research exploring the diverse impacts of COVID-19. Most research, however, tended to focus on public knowledge, practices, and attitudes towards the disease through analyses of cross-sectional survey data.